Answer:
36
Step-by-step explanation:
1
Assuming x = x* and y = y*
(x+y)(x* -xy +y*) = x² - x²y + xy + xy - xy² + y² = x²- x²y + 2xy - xy² + y²
Assuming x != x* and y != y*
(x+y)(x* -xy +y*) = xx* - x²y + xy* + x*y - xy² + yy*
2
Sum of the digits of a two-digit number is 9.
Two digits number = xy
x + y = 9
When we interchange the digits, it is found that the resulting new
number is greater than the original number by 27.
yx = xy + 27
First find all the pairs of numbers that sum to make 9
0 + 9
1 + 8
2 +7
3 + 6
4 + 5
Find the difference between the digits in the form xy and yx.
90 - 09 = 81
81 - 18 = 63
72 - 27 = 47
63 - 36 = 27
54 - 45 = 9